LIQUIFIED NATURAL GAS (LNG) CARRIERS - Daniel Posavec (Rudarsko-geološko-naftni Zbornik, 2010)
Modern liquefied natural gas carriers are double-bottom ships classified according to the type of LNG tank. The tanks are specially designed to store natural gas cooled to -161°C, the boiling point of methane. Since LNG is highly flammable, special care must be taken when designing and operating the ship. The development of LNG carriers has begun in the middle of the twentieth century. LNG carrier storage space has gradually grown to the current maximum of 260000 m3. There are more than 300 LNG carriers currently in operation (the paper is published in Croatian).